Protean Passions: Erasmus, Emotions, and Classical Myth - Essary, Kirk (Erasmus studies, 2020)
The purpose of this essay is to evaluate the manner in which Erasmus employs examples from and the genres of classical mythology in order to explain the emotions, but also to show how he utilizes affective meanings of myths to describe current events. Given Erasmus’ influence, and the burgeoning field of emotions history, my aim is to interject Erasmus more fully into the ongoing conversation about the ways in which emotions were understood in the past. I will do so by considering 1) his adaptation of Quintilian’s taxonomy of emotions as either tragic or comic; 2) his use of classical literature to explore and explain the emotions; and 3) his affective analysis of what he deems the “tragedy” of Martin Luther’s reform movement.